The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1088/0031-9155/54/9/024
|View full text |Cite
|
Sign up to set email alerts
|

The influence of small field sizes, penumbra, spot size and measurement depth on perturbation factors for microionization chambers

Abstract: The purpose of this study was the investigation of perturbation factors for microionization chambers in small field dosimetry and the influence of penumbra for different spot sizes. To this purpose, correlated sampling was implemented in the EGSnrc Monte Carlo (MC) user code cavity: CScavity. CScavity was first benchmarked against results in the literature for an NE2571 chamber. An efficiency increase of 17 was attained for the calculation of a realistic chamber perturbation factor in a water phantom. Calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 39 publications
2
79
0
Order By: Relevance
“…In order to obtain a consistent conversion of absorbed dose in the chamber cavity to absorbed dose in water ͑i.e., the product of all perturbation factors must be equal to the ratio of absorbed dose in water to absorbed dose in the chamber͒, a series of scoring volumes is defined starting at the fully modeled chamber and ending at a small volume of water placed at the centroid of the chamber. Similar to previous studies, [23][24][25] a series of cavity doses is defined as follows: with liquid water ͑density of 1.000 g / cm 3 ͒, and ͑7͒ D w,point : absorbed dose in a 1 mm radius sphere of water placed at the centroid of the chamber and representing absorbed dose at a point in water at the location of measurement.…”
Section: Iib Monte Carlo Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain a consistent conversion of absorbed dose in the chamber cavity to absorbed dose in water ͑i.e., the product of all perturbation factors must be equal to the ratio of absorbed dose in water to absorbed dose in the chamber͒, a series of scoring volumes is defined starting at the fully modeled chamber and ending at a small volume of water placed at the centroid of the chamber. Similar to previous studies, [23][24][25] a series of cavity doses is defined as follows: with liquid water ͑density of 1.000 g / cm 3 ͒, and ͑7͒ D w,point : absorbed dose in a 1 mm radius sphere of water placed at the centroid of the chamber and representing absorbed dose at a point in water at the location of measurement.…”
Section: Iib Monte Carlo Methodsmentioning
confidence: 99%
“…The convention adopted here corresponds to the definitions used in previous publications. [23][24][25] The Exradin A12 and A14 cylindrical ionization chambers ͑Standard Imaging, WI, USA͒ are modeled based on drawings kindly provided by the manufacturer. A series of scoring volumes is created, with the chamber model modified for different, correlated calculations as described above.…”
Section: Iib Monte Carlo Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, Monte Carlo methods have been improved in accuracy such that they are more and more used for the calculation of the dose conversion factor, in particular for the dosimetry under reference conditions using air‐filled ionization chambers. Furthermore, the Monte Carlo‐based decomposition of the dose conversion factor into perturbation factors as described by Bouchard et al . and others turned out to be an effective method for the dosimetry also under nonreference conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ionization chambers that are commonly used in CD fields are not suitable in small and nonstandard radiation fields because of a lack of spatial resolution and accuracy in the absorbed dose measurements caused by the fluence perturbation. Besides this, a recent study that quantified perturbation factors for small ionization chambers in small field dosimetry has revealed that even 0.016 cm 3 volume ionization chambers are not suitable to be used in a 0.8×0.8 cm 2 field [11]. Another disadvantage of the small ionization chamber is the amount of charge collected within the radiation field which can be comparable to the leakage of the dosimetry system itself.…”
Section: Introductionmentioning
confidence: 99%